Correction: A high-throughput microfluidic microphysiological system (PREDICT-96) to recapitulate hepatocyte function in dynamic, re-circulating flow conditions. Issue 19 (5th August 2020) - Tan, Kelly; Coppeta, Jonathan; Azizgolshani, Hesham; Isenberg, Brett C.; Keegan, Philip M.; Cain, Brian P.; Patterson, Abigail J.; Kim, Ernest S.; Kratchman, Louis B.; Rogers, Miles; Haroutunian, Nerses; Newlin, Veronica; et al.
Abstract : Correction for 'A high-throughput microfluidic microphysiological system (PREDICT-96) to recapitulate hepatocyte function in dynamic, re-circulating flow conditions' by Kelly Tan et al., Lab Chip, 2019, 19, 1556–1566, DOI: ; 10.1039/C8LC01262H .